Uma Abordagem para identificação e análise forense de ataques DNS - SOUSA, Robson Everton (2023)
Domain name resolution servers (DNS) perform a key function in establishing access to web pages. Because of their importance, they are constant targets for cyber-attacks, which aim to erase or replace some of their records, causing huge losses for users, companies and institutions worldwide. In Brazil, to prevent such attacks, a legal provision is established that criminally typifies the invasion of computer devices connected to the World Wide Web, which includes attacks on the DNS service. Still, cyber-attack identification is difficult as it depends on the correct application of means of protection, monitoring of network services and extraction and interpretation of data that allow the identification of criminal factors. The present work proposes a computational forensics approach to automatically detect the occurrence of a DNS cache poisoning attack, subsuming the elements that constitute the attack to the legal device, thus identifying the occurrence of a crime.